Religion as a solvent: a lecture - Antônio Flávio Pierucci; Anthony Doyle (Novos Estudos CEBRAP)
Contrary to Durkheim, for whom the role of religion is to reconnect the individual with the society to which he belongs, this essay argues that nowadays religion's social power lies in its capacity to dissolve old religious bonds and lineages. Taking Max Weber's work as its base, the text maintains that the universal religion of individual salvation, the religious form that tends to predominate above all others, works as a device that disconnects people from their mother-culture.